Under scrutiny: Midwives' experience of intrapartum transfer from home to hospital within the context of a planned homebirth in Western Australia - Ball, C.; Hauck, Yvonne; Kuliukas, Lesley; Lewis, Lucy; Doherty, D. (Elsevier Ltd, 2015)
© 2016 Elsevier B.V. Background: Women's experience of homebirth has been a focus of research, with limited international research and no Australian evidence of the experiences of midwives in relation to their experience of intrapartum transfers within the context of a planned homebirth. Objective: To explore the experience of Western Australian midwives involved in an intrapartum transfer from home to hospital. Methods: A descriptive phenomenological study was conducted. Women who elect to have a homebirth in Western Australia have the choice of care from privately practising midwives or a publicly funded program. Midwives who were currently practising or had practised within the past three years and experienced an intrapartum transfer were invited to participate. In-depth interviews were conducted with 13 midwives and data analysed using the Stevick-Colaizzi-Keen method. Results: Analysis revealed an overarching theme "under scrutiny" which captured four themes: "decision to transfer: getting the timing right"; "reception at the hospital: welcoming or not"; "maintaining continuity of carer" and "reflections: coming to terms with the experience". Conclusion: The decision to transfer to hospital represents a profound shift in expectations for the woman and midwife that is often not recognised by hospital staff. Intrapartum transfer is a challenging clinical decision for all parties; midwives, women, partners and health services. Increased effort by maternity health professionals to improve communication and collaboration must be a priority to better support women and their partners who make an informed decision to have a planned homebirth.